(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article aims to analyze the legal nature of the tax and its considerations, as well as the existing relationship with the promotion of Human Rights and the parafiscal function, in a context that takes into account the right to a healthy environment as an integral part of Human Rights. . From the study it is concluded that, with the Declaration of 1948, a new order is established, with a more attentive look at the realization of the common good, according to the collectivity, delimiting the objectives of the State, that is, promoting the realization of the human rights, already recognized worldwide. Recently, the UN Human Rights Council recognized a healthy environment as a Human Right, promoting and supporting environmental struggles, including in the legal sense. Thus, tax activity has become important as one of the main mechanisms for the realization of these rights, seeking to attribute effectiveness to the principle of human dignity, favoring a healthy and balanced environment. The research is bibliographical and focuses on the analysis of scientific production, normative texts and international document of the UN Human Rights Council.